Magnetic Study of Some Transition Metal Chelates with Thiolactic Anilide and Thiolactic p-Toluidide - Srivastava, Miru; Prasad, Ramdeo; Yadav, S.K.; Prasad, S.N. (Asian Journal of Chemistry, 2010)
A series of transition metal compounds with ligands, thiolactic anilide and thiolactic p-toluidide, containing heavier donor sulphur atom, have been synthesised. Characterisations of these compounds were made on the basis of their elemental analysis which showed that metal : ligands ratio is 1 : 2 in all the compounds. The electrical conductivities of these mono-nuclear compounds indicated herein suggest that the compounds are of complex nature. Magnetic studies of the complexes favour the octahedral symmetry of Co(II), Ni(II) and Cu(II) complexes. The other compounds of Hg(II), Pb(II) and Ag(I) are of diamagnetic behaviour.